2018
DOI: 10.17737/tre.2018.4.2.0078
|View full text |Cite
|
Sign up to set email alerts
|

Development of Feed-Forward Back-Propagation Neural Model to Predict the Energy and Exergy Analysis of Solar Air Heater

Abstract: In the present work, Artificial Neural Network (ANN) model has been developed to predict the energy and exergy efficiency of a roughened solar air heater (SAH). Total fifty data sets of samples, obtained by conducting experiments on SAHs with three different specification of wire-rib roughness on the absorber plates, have been used in this work. These experimental data and calculated values of thermal efficiency and exergy efficiency have been used to develop an ANN model. Levenberg-Marquardt (LM) and Scaled C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…e basic principle behind every NN is artificial neurons. It constitutes the process element, which receives the input signal and generates the output for the neighboring process after performing with activation function and associated weights [32]. Figure 1 illustrates the architecture of a simple artificial neuron.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…e basic principle behind every NN is artificial neurons. It constitutes the process element, which receives the input signal and generates the output for the neighboring process after performing with activation function and associated weights [32]. Figure 1 illustrates the architecture of a simple artificial neuron.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Basic steps flow chart of ANN simulation technique [71] The basic steps of ANN simulation technique are shown in flow chart Figure 6. These important steps are followed in ANN prediction [5,65]. 1.…”
Section: Sum Of Square Errormentioning
confidence: 99%
“…They also concluded that the LM based ANN model was best model. [65] developed feed forward neural network model to predict the energy and exergy efficiency of transverse wire rib roughened solar air heater. To achieve this aim, they collected 50 sets of experimental data and calculated values of energy and exergy efficiencies.…”
Section: Performance Prediction Of Solar Water/ Air Heating Systems Umentioning
confidence: 99%
“…Sahu and Prasad [25] found that a relative roughness height e/Dh = 0.0422, a relative roughness pitch P/e = 10, and a relative angle of attack /90 = 0.3333 yielded the maximum exergy efficiency for solar air heaters with arcshaped wires. In particular, Ghritlahre et al, [31,33,34] and Ghritlahre [32] recommended the use of the artificial neural network (ANN) technique to predict the energy and exergy performance of a SAH due to its high accuracy.…”
Section: Exergy Efficiencymentioning
confidence: 99%